Treino de jovens basquetebolistas de Fortaleza-CE - Campos Vieira, L.; Alcantara Sampaio, T.; Aires, H.; Treter Goncalves, G. H.; Adelar Abaide Balbinotti, C.; Gonzalez, R. H. (Revista Ciencia del Deporte, 2020)
The objective of the present study was to verify the training frequency of basketball technical-sportive foundations in young athletes from Fortaleza-Ce. This is a ex-post-facto study involving 39 young men and women aged 11 to 16 years (child and juvenile). The information was collected in two moments, during some games of the 3rd edition of the Superleague Basketball School of Ceará and in the training environment of the teams, through the ITTB-50 (Inventory of Technical Training and Sports Basketball), instrument that groups 50 items related to the main technical-sports fundamentals: dribbling, passing, throwing, rebounding and marking. The treatment of the data was based on descriptive statistics of central tendency and dispersion (mean and standard deviation) with the assistance of SPSS 20.0 softwares. The evidence found indicates that Fortaleza-Ce team coaches, from the infant and juvenile categories, place greater emphasis on offensive fundamentals compared to the defensive fundamentals.